Anti-Realist Arguments in Philosophy - Japertas, Mindaugas (Problemos, 2001)
The article aims to reveal the incoherence of realism conceived as an attitude concerning reality and hence as a certain metaphysical theory of reality. The traditional philosophical realist viewpoint is considered as inconsistent, unintelligible and incommunicable. The incoherence of realism is disclosed by the critical examination of theoretical difficulties which are inevitable for the conceptions of correspondence and reference. The article also presents arguments in favour of the alternative anti-realist interpretation. The specific form of the theory of meaning is considered as the essential condition of well-founded anti-realism. Such a theory of meaning refuses to uphold the objectivist notion of truth and replaces the latter by the pragmatist concepts of verification and assertibility. Besides that, it focuses on the epistemic aspect of meaning (i.e., the sense of a linguistic unit) and gives account of the overall phenomenon of indeterminacy of meaning in natural languages. From a logical and a philosophical point of view most important consequences are due to the rejection of the fundamental principle of bivalence by anti-realism.